Underwater Acoustic Communication Based on Hyperbolic Frequency Modulated M-ary Binary Orthogonal Keying - Yuan Fei; Lin Xiao-Yang; Wei Qian; Cheng En (Institute of Advanced Engineering and Science, 2014)
In this paper, we propose the HFM-MBOK modulation thecnology based on the frequency bands allocation which is suitable for underwater acoustic communication. The solution have characteristic of constant envelope. Under the guidace of the theory, we test the practicability of the system throuth Matlab simulation. And the sistem used MFSK-MBOK cascaded technology and reduced calculation amount significantly. Finally, the underwater acoustic communication system we proposed has been tested in the pool. The experiment results show that the system is able to achieve a robust and reliable communcation under the condicaions of low signal-to noise ratio and strong multipath envirement.